Potensi Limbah Kayu Industri Mebel untuk Produk Home Accessories - Rahmawan Dwi Prasetya (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2015)
Special Region of Yogyakarta has a lot of the furniture industry. Most of the industries are oriented to export products, while others tend to market them on the domestic market. The existence of the industry has a positive impact on the economy of the Special Region of Yogyakarta. The frequent furniture production that tends to increase over time, as a matter of fact, needs more raw materials. This rise of furniture production gives rise to a great volume of waste because it is not possible to reuse it to make furniture. The waste out of every 18-20 m3 wood are mainly in the form of 5-6 m3 of sawdust and 2-2.5 m3 wood chips. This paper describes the results of two workshops related to the utilization of wood waste. Workshop I was done by inviting participants from Small And Medium Enterpreneurship (SME) throughout Bantul by socializing design trends and international market to enable SME in Bantul can customize its design with the condition. Workshop II conducted as a follow-up to the workshop I, with output in accordance with the design trends of 2010.Keywords: meubel, home accessories, waste